Effect on survival after myocardial infarction of long-term treatment with phenytoin. Issue 12 (December 1978) - Peter, T; Ross, D; Duffield, A; Luxton, M; Harper, R; Hunt, D; Sloman, G
Abstract : A prospective, randomised, open trial was performed in 150 patients to test for any beneficial effects on 2-year mortality of long-term antiarrhythmic therapy with phenytoin in patients with acute myocardial infarction. Patients were stratified according to age, sex, past history of myocardial infarction, and the presence of absence of electrical or mechanical complications in the course of acute infarction. They were then randomised to treatment or control groups (74 v. 76). The former received phenytoin in doses aimed at maintaining plasma phenytoin levels between 40 and 80 mumol/litre. All patients entered the study before discharge from the coronary care ward. Plasma phenytoin levels were in the therapeutic range in between 51 and 75 per cent of subjects at any follow up visit. There were 19 withdrawals from the treatment group, 10 of which were the result of side effects. There were 5 withdrawals from the control group. According to the original intention to treat, there were 18 deaths at 2 years in the treatment group and 14 deaths in the control group. There was no reduction in the incidence of instantaneous or sudden deaths. Deaths on treatment were not associated with a low phenytoin plasma level. Phenytoin treatment showed no beneficial effects on mortality and was associated with a high incidence of side effects.